Evaluation of Smart Home Platform Based on Blockchain - Nugraha, I Gde Dharma; Yoarana, Hosea (International Journal of Electrical, Computer, and Biomedical Engineering, 2024)
A smart home consists of various sensors and actuators that can communicate with each other. In addition, various home appliances have similar capabilities. Therefore, the smart home became one of the applications of the Internet of Things (IoT). In this application, arise the challenges caused by the integration of various devices that came from various vendors have a different data format and keeps the data's security. Blockchain has been proposed as one solution to address these challenges. In this paper, we investigate and evaluate the performance of the blockchain-based solution for smart home IoT. Our experiment results show that the Blockchain can secure the IoT-based smart home, but it took47% longer for packet delivery.